ELECTRONIC BANKING - S. Kovačević, Maja; S. Đuričić, Milan (Law - Theory and Practice, 2014)
Electronic money and electronic banking represents a result of the wide application of the information and communication technologies. The paper contains an analysis of characteristics, factors of development and economic effects of the electronic money and electronic banking. In this paper we start from the hypothesis that the electronic money and electronic banking is necessary as a form of marketing communication, because it positively affects the speed and efficiency of operations.